Phenylketonuria in the adult patient. (3rd June 2019) - Ceberio, Leticia; Hermida, Álvaro; Venegas, Eva; Arrieta, Francisco; Morales, Montserrat; Forga, Maria; Gonzalo, Montserrat
ABSTRACT: Introduction : Phenylketonuria (PKU) is an inborn error in phenylalanine metabolism that can cause irreversible brain damage if it is untreated. In the last decades, the prognosis of this disease has evolved due partly to the introduction of the newborn screening (NBS) programs and the recommendation of lifelong treatment. However, despite this and the significant number of adults with PKU, the available evidence about this group of patients is limited. Areas covered : The aim of this review is to describe the main challenges of the current management of PKU in adults, discussing the important aspects of diagnosis, treatment and follow-up of PKU. A separate section has been dedicated for the special case of PKU in pregnant women whose care is extremely important to prevent maternal phenylketonuria syndrome (Mpku). Experts opinion : The management of PKU in adult patients requires an efficient transition program to specialized metabolic units, new therapies that improve the adherence and quality of life of the patients and a follow-up consisting of metabolic and nutritional monitoring and control of potential comorbidities. To prevent Mpku, the female patients in reproductive age require a special care based on metabolic control and other nutritional parameters prior to conception and during the pregnancy.